High flow nasal cannula (HFNC) with Heliox decreases diaphragmatic injury in a newborn porcine lung injury model. Issue 12 (5th February 2014) - Jassar, Romal K.; Vellanki, Haritha; Zhu, Yan; Hesek, Anne; Wang, Jordan; Rodriguez, Elena; Wu, Jichuan; Shaffer, Thomas H.; Wolfson, Marla R.
Summary Background High flow nasal cannula (HFNC) improves ventilation by washing out nasopharyngeal dead space while delivering oxygen. Heliox (helium–oxygen gas mixture), a low‐density gas mixture, decreases resistance to airflow, reduces the work of breathing, and facilitates distribution of inspired gas. Excessive lung work and potential injury increases the workload on the immature diaphragm predisposing the muscle to fatigue, and can lead to inflammatory and oxidative stress, thereby contributing to impaired diaphragmatic function. We tested the hypothesis that HFNC with Heliox will decrease the work of breathing thereby unloading the neonatal diaphragm, and potentially reducing diaphragmatic injury. Methods Spontaneously breathing neonatal pigs were randomized to Nitrox (nitrogen–oxygen gas mixture) or Heliox, and studied over 4 hr following oleic acid injury. Gas exchange, pulmonary mechanics indices, and systemic markers of inflammation were measured serially. Diaphragm inflammation biomarkers and histology for muscle injury were assessed at termination. Results Heliox breathing animals demonstrated decreased respiratory load and work of breathing with lower pressure‐rate product, lower labored breathing index, and lower levels of diaphragmatic inflammatory markers, and muscle injury score as compared to Nitrox. Conclusion These results suggest that HFNC with Heliox is a useful adjunct to attenuate diaphragmatic fatigue in the presence of lung injury by unloading the diaphragm, resulting in a more efficient breathing pattern, and decreased diaphragm injury. Pediatr Pulmonol. 2014; 49:1214–1222. © 2014 Wiley Periodicals, Inc.